2021
DOI: 10.7150/jca.48589
|View full text |Cite
|
Sign up to set email alerts
|

A Noninvasive Assessment of Tumor Proliferation in Lung cancer Patients using Intravoxel Incoherent Motion Magnetic Resonance Imaging

Abstract: Ki-67 is a nuclear antigen widely used in routine pathologic analyses as a tumor cell proliferation marker for lung cancer. However, Ki-67 expression analyses using immunohistochemistry (IHC) are invasive and frequently influenced by tissue sampling quality. In this study, we assessed the feasibility of noninvasive magnetic resonance imaging (MRI) in predicting the Ki-67 labeling indices (LIs). A total of 51 lung cancer patients, including 42 non-small cell lung cancer (NSCLC) cases and nine small cell lung ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 39 publications
(48 reference statements)
5
23
0
Order By: Relevance
“…As shown in previous studies (7,16,17), tumor cell death by necrosis or apoptosis caused by anticancer drugs reduces cell density and increases the tumor extracellular volume in early response. Recent study showed D values from IVIM were negatively correlated with Ki-67 expression, which is likely that the highly proliferative tumors (high Ki-67 expression) had higher inner structural complexities due to increased cellularity, vascular hyperplasia, and necrosis (7), and this is the biological basis for the observed increase in ADC and D after treatment. Furthermore, because ADC is obtained from a mono-exponential model using diffusion-weighted MR imaging which is subject to errors introduced by the microcirculation of blood, D showed a higher performance at predicting response to therapy than ADC.…”
Section: Figure 2asupporting
confidence: 55%
See 2 more Smart Citations
“…As shown in previous studies (7,16,17), tumor cell death by necrosis or apoptosis caused by anticancer drugs reduces cell density and increases the tumor extracellular volume in early response. Recent study showed D values from IVIM were negatively correlated with Ki-67 expression, which is likely that the highly proliferative tumors (high Ki-67 expression) had higher inner structural complexities due to increased cellularity, vascular hyperplasia, and necrosis (7), and this is the biological basis for the observed increase in ADC and D after treatment. Furthermore, because ADC is obtained from a mono-exponential model using diffusion-weighted MR imaging which is subject to errors introduced by the microcirculation of blood, D showed a higher performance at predicting response to therapy than ADC.…”
Section: Figure 2asupporting
confidence: 55%
“…This means the D value decreased when tissue contained a high number of cells and ratio of nucleus to the cytoplasm, or with smaller extracellular space because of the diffusion movement of water molecule was limited (15). As shown in previous studies (7,16,17), tumor cell death by necrosis or apoptosis caused by anticancer drugs reduces cell density and increases the tumor extracellular volume in early response. Recent study showed D values from IVIM were negatively correlated with Ki-67 expression, which is likely that the highly proliferative tumors (high Ki-67 expression) had higher inner structural complexities due to increased cellularity, vascular hyperplasia, and necrosis (7), and this is the biological basis for the observed increase in ADC and D after treatment.…”
Section: Figure 2amentioning
confidence: 64%
See 1 more Smart Citation
“…CDKN3 overexpression is prognostic of poor overall survival in lung adenocarcinoma ( Fan et al, 2015 ). Ki-67 is expressed in the active phases of the cell cycle, including G1, G2 and S, and has been used as an independent biomarker to predict prognosis in patients with lung cancer ( Zheng et al, 2021 ). The centromeric protein CEP55, encoded by the CEP55 , is widely expressed in different types of tissues, especially in proliferating tissues ( Eloubeidi et al, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…The possible reason is that IVIM effectively eliminates the in uence of capillary micro perfusion on diffusion coe cient compared with single index DWI. Based on the obvious negative correlation between ADC and D value with Ki-67, the increase of Ki-67 expression may suggest a stronger tumor cell proliferation activity, tighter cell arrangement, smaller extracellular space, higher nucleocytoplasmic ratio and more organelles, which signi cantly reduces the intracellular space, shows more signi cant restriction on the free diffusion of water molecules and therefore shows lower ADC and D (21)(22)(23)(24). D * and f values mainly re ect micro perfusion of new capillaries in tumor cell space, which is related to cell density, cell necrosis and bleeding.…”
Section: Discussionmentioning
confidence: 99%